2015
DOI: 10.1016/j.yjmcc.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from multi-scale modeling of the failing heart

Abstract: Heart failure constitutes a major public health problem worldwide. Affected patients experience a number of changes in the electrical function of the heart that predispose to potentially lethal cardiac arrhythmias. Due to the multitude of electrophysiological changes that may occur during heart failure, the scientific literature is complex and sometimes ambiguous, perhaps because these findings are highly dependent on the etiology, the stage of heart failure, and the experimental model used to study these chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 146 publications
1
9
0
Order By: Relevance
“…Interestingly, the optimization algorithm did not reveal large differences in hemodynamic lumped parameters, but it attributed instead the discrepancies in ejection fraction and cardiac phase duration to the S a and τ 2 parameters, which modulate cardiac contraction efficiency and decay time of calcium transients, respectively. More specifically, our analysis suggested that the HF MRI measurements could be explained by smaller S a values and longer τ 2 times, which is in agreement with experimental findings on heart failure myocyte phenotypes, which are less effective in contracting partially due to dysfunctional calcium handling [39, 40].…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, the optimization algorithm did not reveal large differences in hemodynamic lumped parameters, but it attributed instead the discrepancies in ejection fraction and cardiac phase duration to the S a and τ 2 parameters, which modulate cardiac contraction efficiency and decay time of calcium transients, respectively. More specifically, our analysis suggested that the HF MRI measurements could be explained by smaller S a values and longer τ 2 times, which is in agreement with experimental findings on heart failure myocyte phenotypes, which are less effective in contracting partially due to dysfunctional calcium handling [39, 40].…”
Section: Discussionsupporting
confidence: 87%
“…6). Downregulation of repolarizing K ϩ currents (with subsequent action potential prolongation) is a common theme in heart failure (17,46), and our data suggest a potential contribution of K 2p 17.1 in the pathogenesis of nonischemic heart failure. Furthermore, we report significant prolongations of APD 90 and APD 50 in siRNA-mediated silencing of K 2p 17.1 in iCells (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, understanding the mechanisms contributing to fibrosis will help us identify therapeutic targets. In this study, we identified several genes associated with fibrosis, some of which have been reported in literature, such as ELN and POSTN [47,48]. In addition, we identified several novel fibrosis associated genes for further validation, such as NR4A3, PTGDS, TNC, miR-190a, and miR-708-5p.…”
Section: Discussionmentioning
confidence: 75%